Immediate effects of Vojta Therapy on gait ability in down syndrome patients: a pilot study - Qian, Guoping; Perzanowska, Ewelina; Kozakiewicz, Mirela; Ewertowska, Paulina; Yu, Hongli; Ossowski, Zbigniew (Frontiers in Neurology, 2025)
BackgroundVojta Therapy (VT) is a neurorehabilitation approach that targets ontogenetic postural function and automatic body posture control. Research has shown its potential to enhance gait ability. However, limited evidence exists regarding its immediate effects on individuals with Down syndrome (DS).ObjectivesThis study aimed to assess the immediate effects of one session VT on spatiotemporal gait parameters in individuals with DS.DesignA non-randomized pilot study was conducted.MethodsSixteen individuals with DS (mean age: 17.88 ± 4.57 years, 8 males) participated in this study. Each received a single VT session administered by an experienced physiotherapist. Spatiotemporal gait parameters before and after VT were analyzed using the Vicon motion capture system.ResultsSignificant improvements were observed in walking speed (m/s), cadence (steps/min), right step time (s), step length (cm), stride length (cm), and double support time (%GC) following the VT session (P < 0.05). These findings suggest that VT may offer immediate benefits in improving gait parameters for individuals with DS.ConclusionsFuture large-scale studies with more robust designs are necessary to explore the long-term effects of extended VT programs.